Macropropagation as an innovative technology: lessons and observations from projects in Cameroon - Lefranc, L.M.; Lescot, T.; Staver, Charles; Kwa, M.; Michel, I.; Nkapnang, I.; Temple, L.; Dubois, E. (International Society for Horticultural Science, 2010)
The availability and quality of plantain (Musa spp.) planting material is one of the main constraints for the intensification of this crop. Farmers often use suckers infested with pest and diseases as their only source of planting material. In three provinces of Cameroon, three projects promoted diverse new technologies, including the ‘plantlet from stem bits’ (PIF) horticultural propagation method developed by the Centre Africain de Recherches sur Bananiers et Plantains (CARBAP) and new varieties from the Fundación Hondureña de Investigación Agrícola (FHIA), the International Institute of Tropical Agriculture (IITA) and CARBAP to improve plantain production. The training approaches of the projects varied, but depending on the project, farmers were also trained in agronomic practices, agro-processing and marketing. The objective of this study was to identify lessons for the use of horticultural multiplication methods to improve the production of plantain among smallholder farm households based on the experience of the three projects. Project and other documentation was reviewed, interviews with key participants, 44 farmers and nursery operators and 55 other stakeholders, were conducted and field visits carried out. Five lessons were identified. The PIF method was considered of great potential to contribute to improved quantity and quality of planting material. Although PIF plants are more expensive than traditional suckers, the costs and infrastructure needed are within reach of small growers, especially scaled down for on-farm use. PIF nurseries should be set up close to fields to be planted, on-farm, among neighboring farmers or through growers’ associations. The PIF method is very useful in making more planting material available for newly introduced cultivars or for increasing the planting material of superior mother plants of preferred local cultivars. Growers, nursery operators, extension workers and scientists should all take part in developing minimum specifications for the production of good quality planting materials. Greater monitoring of the performance of PIF plants compared to traditional suckers in growers’ fields should also be prioritized.